Polysulphated glycosaminoglycans modulate transcription of interleukin-1β treated chondrocytes in monolayer culture - Mertens, W. D.; MacLeod, J. N.; Fubini, S. L.; Vernier-Singer, M.; Nixon, A. J.; Todhunter, R. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The ability of polysulphated glycosaminoglycans (PSGAGs, Adequan®) to modulate the transcription of major articular cartilage matrix proteins and enzymes was examined. Northern blot analyses were used to compare steady-state mRNA levels of type-II procollagen, aggrecan core protein, matrix metalloproteinase (MMP)-1, MMP-3, tissue inhibitor of metalloproteinase (TIMP)-1, and TIMP-3 in equine chondrocytes grown in monolayer culture. The groups included: control, low-dose (0.1mg/ml) Adequan®, high-dose (1.0mg/ml) Adequan®, IL-1 β (10ng/ml), IL-1 β with low-dose Adequan®, and IL-1 β with high-dose Adequan®. The responses (p<0.05) to treatment were compared with one-way analysis of variance and post hoc least significant difference test. Interleukin-1 β significantly decreased steady-state levels of type-II procollagen (0.5x) and aggrecan core protein (to undetectable levels) and significantly increased MMP-1 (11.7x), MMP-3 (1.8x), TIMP-1 (1.9x), and TIMP-3 (5.1 x). Adequan® alone significantly increased steady-state mRNA levels of type-II procollagen (1.6x) and decreased MMP-1 (0.3x at high-dose only), MMP-3 (0.5x), and TIMP-1 (0.3x at high-dose only). In IL-1 β-treated chondrocytes, Adequan® significantly increased steady-state mRNA levels of type-II procollagen (1.4x of IL-1 β-treated levels), aggrecan core protein (IL-1 β -treated had no detectable expression), and MMP-3 (3.6 x at high dose) and significantly decreased steady-state mRNA levels of MMP-1 (0.3 x), and TIMP-1 (0.2x). This study is the first to demonstrate that Adequan® alters steady-state mRNA levels of key matrix proteins and enzymes; that it counteracts some of the deleterious effects of IL-1 β; and that these effects are in part dose-dependent.
Keywords: Chondrocyte; mRNA; polysulphated glycosaminoglycan; interleukin-1; equine